A comparative review of 1, 004 orthopaedic trauma patients before and during the COVID-19 pandemic. (September 2020) - Dayananda, K. S. S.; Mercer, S. T.; Agarwal, R.; Yasin, T.; Trickett, R. W.
No abstract available